Air-impingement freezing of peeled shrimp: Analysis of flow field, heat transfer, and freezing time. (March 2019) - Yang, Dazhang; Xie, Jing; Tang, Wan; Wang, Jinfeng; Shu, Zhitao
The air-impingement freezing technique is a fast and efficient freezing method, which is widely used in food freezing and electronic industry. A novel air-impingement freezing machine was set up to investigate the food freeze. The freezing process of peeled shrimps by air-impingement freezing technique was studied experimentally and numerically. The freezing time of shrimp (150 count/lb) from +11°C to −18°C was about 100–140 s. The flow field and temperature distribution of peeled shrimp were studied by the solidification and melting model in FLUENT 6.3. The results show that the air jet flows away from the surface of the shrimp after the separation points so that the flow field and heat transfer were bad in the separation resign. In addition, the food freezing time of natural convection and air-impingement was compared, and the result shows that the air-impingement freezing time is about one-tenth than the natural convection freezing in freezer. In order to optimize the air-impingement freezing, H/D 's value was adjusted in the range of 4–8. The result indicates that the freezing time was increasing with the increase in H/D value, and H/D was recommended to be 6 in the impingement freezing.